Case Series Report: Subarachnoid Hemorrhage and ICU Management - Retnaningsih; Tugasworo, Dodik; Andhitara, Yovita; Ardhini, Rahmi; Kurnianto, Aditya; Daynuri; Harianto, Erlangga Pradipta (Medica Hospitalia : Journal of Clinical Medicine, 2023)
Background: Subarachnoid hemorrhage is a neurological syndrome with complex systemic complications. Rupture of an intracranial aneurysm causes acute extravasation of arterial blood under high pressure into the subarachnoid space and often into the brain parenchyma and ventricles. Bleeding triggers a complex series of events, which can ultimately lead to early brain injury, delayed cerebral ischemia, and systemic complications. Cases: There were six cases of subarachnoid hemorrhage. Some patients come clinically with severe headache and loss of consciousness. The patient has been treated quickly and aggressively and even put on a ventilator for complications of respiratory failure, support for shock and management of aneurysm clipping and EVD. Rapid and precise diagnosis in the management of patients with SAH is of paramount importance, within the first few hours after the onset of SAH. The risk for early neurologic damage and high rates of severe long-term complications necessitated aggressive early management. Conclusion: Rapid diagnosis and attentive management of patients with SAH are essential, as early deterioration is possible within the first few hours after the onset of SAH. The risk for early neurologic damage and high rates of severe long-term complications necessitated aggressive early management. Prevention and Management of Complications. The most common complications were pneumonia, aspiration, respiratory failure/distress, sepsis and imbalance electrolyte (hyponatremia). Approximately 50% of deaths after SAH are due to medical complications.